Implementation of Collaborative Learning in Higher Education Environment - Soetam Rizky Wicaksono (Journal of Education and Learning (EduLearn), 2013)
The need of  improvement in learning process, especially in higher education environment, has already begun a dilemma for many lecturers. Many experts has already agreed that one of the success factor in learning process improvement is creating collaboration among students. This pre-eliminary action research tried to implement collaborative learning from small groups using simple task and escalating into large group with more complicated collaborative framework. Although there is no quantification result in this research, the questionnaire result has already proven that collaborative learning is feasible in higher education environment. However, further research in term of collaborative learning can be done easier using the result from this research.